REMODELING BUSINESS FOR SURVIVABILITY ON CARPET RETAIL STORES IN INDONESIA - Maureen Nuradhi; Benazir Fahim; Eric Harianto; Riduan Mas’ud; Denpharanto Agung Krisprimandoyo; Maimunah Johari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Covid-19, the novel coronavirus, has brought the entire world to a halt. The virus was first reported by several local health officials in Wuhan, Hubei Province, China in late December 2019 (Zhu, et al., 2020). Although the infection had spread to hundreds of individuals in Wuhan by early January 2020, with roughly 11 million people placed under quarantine, the first diagnosis showed no evidence of such a disastrous impact on public life (Woodward, 2020). As the number of afflicted patients increased over the month, WHO declared the disease as a Public Health Emergency of International Concern (PHEIC) on January 30, 2020 (Harchandani & Shome, 2021). By March 11, 2020, Covid-19 has been declared a pandemic (WHO, 2020). The pandemic’s harmful effects have been delineated in all aspects of life, and have had economic, political, social, and psychological ramifications (Bretas & Alon, 2020); (Ratten, 2020); (Sigala, 2020). Many economists regard the epidemic as a metaphorical “black swan” event, that is, unexpected, the unanticipated occurrence of immense magnitude and severe repercussions that profoundly transform the political and economic landscape (Winston, 2020) (Gregurec, Furjan, & Pupek, 2021), which caused business failures (Kuckertz, et al., 2020); (Amoah, Khan, & Wood, 2021). Following the global situation, Indonesia is also dealing with the same issue, with the Covid-19 pandemic influencing Indonesia’s economic activities and business sectors. The decline in growth trends in 2020 and 2021 in the effects of the Covid-19 pandemic can also be seen in the textile and garment industry sector in Indonesia as quoted from data industry research compiled from the Badan Pusat Statistik (BPS) and Bank Indonesia (BI).